Wheat Variety Response to Seeding Rate in Kansas During the 2015–2016 and 2016– 2017 Growing Seasons - R. P. Lollato; G. Zhang; B. R. Jaenisch; R. Maeoka; L. Bonassi; A. K. Fritz (Kansas Agricultural Experiment Station Research Reports, 2018)
Plant density is among the major factors determining a crop’s ability to capture resources such as water, nutrients, and solar radiation; therefore, different wheat varieties might require different seeding densities to maximize yield. The objective of this project was to better understand the response of different wheat varieties to seeding rate. Two field experiments were conducted during 2015–2016 and repeated during 2016–2017, evaluating seven wheat varieties subjected to five different seeding rates (0.6, 0.95, 1.3, 1.65, and 2.0 million seeds/a). Crop was managed for a 70 bu/a yield goal and pests were controlled using commercially available pesticides. Final stand and grain yield were measured, and all statistical analyses were performed for relating emerged plants per acre to grain yield. At each individual environment and across varieties, grain yield usually was maximized at approximately 0.9 million emerged plants per acre. There were significant differences among varieties in grain yield, with Joe and Tatanka usually outperforming the remaining tested varieties. Across environments, grain yield usually was maximized at populations between 0.6 and 0.7 million plants per acre for less responsive varieties (1863, Everest, and Tatanka), at approximately 0.9 million plants per acre for average responsive varieties (Joe, Bob Dole, KanMark, and Zenda), and more than 1.05 million emerged plants per acre for more responsive varieties (Larry and AG Icon). These preliminary data suggests that there is the potential to manage each wheat variety according to its individual tillering potential; however, more data are needed to make definite conclusions about each variety’s optimum seeding rate. Thus, this experiment is currently being conducted at five sites during the 2017–18 growing season.
Keywords: wheat seeding rates; Kansas wheat; Agronomy field research; wheat varieties